RETORIKA DAKWAH K.H.MUHAMMAD DAINAWI PADA PENGAJIAN A’ISYAH DESA PULAU PANGGUNG SUMATERA SELATAN - Sarwinda Sarwinda (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Preaching is an honorific duty in which a muslim delivers his knowledge of Islamic teaching to his/her society sincerely. Hence, the preacher should know elements that play pivotal roles in delivering such messages successfully. Some of those elements are meaningfulness, rightness, the power of context, understanability and reasonability. It is an art for a preacher to guide the lost soul, opening path for the light to get into people’s heart, cure the wounded, arouse the defeated, voice the truth with freshness. One of many succesfull preacher who has been known as a succesfull preacher in Indonesia is K.H. Muhammad Dainawi. Hence, the aim of this research is to understand the rhetoric of preaching of K.H. Muhammad Dainawi. It will also explore many responses given by the audience on K.H.Muhammad Dainawi’s preaching. In designing this research, the writer uses descriptive research. Collecting data techniques in this research are documentation as the main method, observation, and interview. Keywords: Rhetoric, Preaching, Recitation